Gathering to save a nation : Lincoln and the Union's war governors - Engle, Stephen Douglas (Civil War America (Series), 2016)
In this rich study of Union governors and their role in the US Civil War, Stephen D. Engle examines how these politicians were pivotal in securing victory. While providing detailed and engaging portraits of these men, their state-level actions, and their collective cooperation, Engle brings into new focus the era's complex political history.